Fiscal Federalism, Tax Independence and Social Enhancement - Omodero, Cordelia Onyinyechi (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The tax autonomy of Nigeria's three tiers of government is examined in this study to estimate the value of revenue fiscal decentralization in increasing citizens' social welfare. Nigeria is a developing country that follows fiscal federalism by allocating resources to the three tiers of government and equally allowing them specific amounts of tax revenue collection based on the requirements of the Federal Republic of Nigeria's 1999 constitution's second schedule part II. The main goal is to affect social development in all parts of the country. Thus, this study uses secondary data from 2007 to 2020 and analyzes it using a multiple regression approach to determine the influence of each tier of government's tax autonomy on residents' social welfare. According to the findings of this research, the federal government's fiscal autonomy empowers social development more than the other two levels of government (state and local governments). The policy conclusion is that the tax autonomy of the three tiers of government may need to be reassessed in order to offer additional taxing powers to lower-level governments for better economic growth prospects. As a result, the research advises revamping the country's overall fiscal system in order to promote social growth across states, local governments, and the whole nation.